Minimally Invasive Autopsy: A New Paradigm for Understanding Global Health? - Peter Byass (PLoS Medicine, 2016)
Peter Byass reflects on the potential niche for minimally invasive autopsies in determining cause-of-death in low- and middle-income countries.